2010 the 2nd Conference on Environmental Science and Information Application Technology 2010
DOI: 10.1109/esiat.2010.5568420
|View full text |Cite
|
Sign up to set email alerts
|

Notice of Retraction: Effect of Asparagus polysaccharide on the number and activity of erythrocyte complement receptor 1(CD35) of S180 mice

Abstract: To study the effect of Asparagus officinalis polysaccharide on the number and activity of erythrocyte complement receptor 1(CD35) in S180 mice. Red blood cells from mice venous blood are labeled by rat anti-mouse CD35 monoclonal antibody and FITC-conjugated goat anti-mouse antibody. Using flow cytometry, we determined the number of CR1. Using microscope, we studied the adherence between erythrocyte immunity and C3b receptor or tumor-cell by RBC-C3bRR and DTER. Comparing the mean value of the number of CR1 on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…ASP, an extract from asparagus, is a type of polysaccharide which has been shown to be the main active ingredient of asparagus involved in its antitumor and apoptosis-promoting activities. In our previous studies, we reported that ASP has relatively few side effects compared with common antitumor drugs and can inhibit tumour cell proliferation, promote tumour cell apoptosis, and prolong the survival of tumour-bearing animals [3135]. The effects of ASP on the growth, migration, and invasion of Hep-G2 cells under hypoxic conditions have also been reported by members of our research group [36].…”
Section: Introductionmentioning
confidence: 54%
“…ASP, an extract from asparagus, is a type of polysaccharide which has been shown to be the main active ingredient of asparagus involved in its antitumor and apoptosis-promoting activities. In our previous studies, we reported that ASP has relatively few side effects compared with common antitumor drugs and can inhibit tumour cell proliferation, promote tumour cell apoptosis, and prolong the survival of tumour-bearing animals [3135]. The effects of ASP on the growth, migration, and invasion of Hep-G2 cells under hypoxic conditions have also been reported by members of our research group [36].…”
Section: Introductionmentioning
confidence: 54%